Network Potentials - Subhadip Chakrabarti; Robert Paul Gilles (University of Bonn, Bonn Graduate School of Economics (BGSE), 2005)
A network payoff function assigns a utility to all participants in a (social) network. In this paper we discuss properties of such network payoff functions that guarantee the existence of certain types of pairwise stable networks and the convergence of certain network formation processes. In particular we investigate network payoff functions that admit an exact network potential or an ordinal network potential. We relate these network potentials to exact and ordinal potentials of a non-cooperative network formation game based on consent in link formation. Our main results extend and strengthen the current insights in the literature on game theoretic approaches to social network formation.
Keywords: C79; C72; D85; 330; Network formation; pairwise stability; potential functions